Hubungan Komunikasi dan Kepastian Waktu dengan Kepuasan Pasien BPJS Rawat Jalan di Wilayah Kerja Puskesmas Nambo Tahun 2016 - Risky, Sartini (Jurnal Gizi Ilmiah, 2016)
Based on the results of the initial survey conducted by researchers at the Nambo Health Center from 10 visitors there were 6 visitors who still showed patient dissatisfaction with the welcome received when visiting, did not say hello, the staff was not friendly, the patient was at the Puskesmas before the officer. The purpose of this study was to determine the relationship between communication and time certainty with outpatient BPJS patient satisfaction in the Nambo Health Center Work Area in 2016. The type of research used in this research is analytic research with a “Cross Sectional Study” approach. The population in this study were all BPJS patients who visited the Nambo Health Center from January to March 2016 totaling 571 patients. The sampling technique in this study is a non-probability sampling technique with the type of accidental sampling with a total sample of 72 respondents. The statistical test used was the Chi Square test and the p test. The results showed that there was a strong relationship between communication and BPJS patient satisfaction in the Nambo Health Center Work Area (X2 = 37.540 and p = 0.750), there was a moderate relationship between time certainty and BPJS patient satisfaction in the Nambo Health Center Work Area (X2 = 5.530 and p = 0.305) It is recommended for the Nambo Health Center to improve health services, especially in communicating (giving greetings and greetings when receiving visiting patients), as well as providing certainty of time for visitors (officers who are on time).